CONSUMER’S SATISFACTION ON BENGKEL MOTOR AHASS 1605 SETURAN YOGYAKARTA BASED ON SERVICE QUALITY DIMENSION - Wisnalmawati Wisnalmawati (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The objective of this study is to elaborate the differences of customer—in this case university students—satisfactions towards service quality of Bengkel Motor AHASS 1605 Seturan Yogyakarta. Samples in this study are university students who are customer of the bengkel. Purposive sampling combined with simple random sampling was applied to select 100 respondents. Primary data regarding those variables under study were collected using questionnaires. Data were analyzed using Paired Sample t-test. Results of the study showed that there were differences on customer satisfaction based on service quality dimensions. It implies that management of the bengkel is required to formulate better marketing strategies that lead to better service quality and its associated dimensions.Key words: customer satisfaction; service quality dimensions; marketing strategy.